ChemInform Abstract: Cobalt‐Catalyzed Hydrosilation/Hydrogen‐Transfer Cascade Reaction: A New Route to Silyl Enol Ethers. Issue 51 (17th December 2013) - Lyons, Thomas W.; Brookhart, Maurice
Abstract A novel cobalt‐catalyzed method for the synthesis of silyl enol ethers from ketones is described.